The Influence of the Creative Problem Solving Learning Model on Student Activity in PKN MI An-Nur Subjects - Azka, Siti Nisrinaa Nur; Mudiyanto, Heru; Laily, Idah Faridah (UIN Siber Syekh Nurjati Cirebon, 2024)
The issue of low student engagement in Civic Education (PKn) at the Madrasah Ibtidaiyah level has become a major concern in improving the quality of learning processes. This study aims to examine the effect of the Creative Problem Solving (CPS) learning model on the activeness of fourth-grade students at MI An-Nur. The research employed a pre-experimental design with a pretest-posttest one group design and involved 31 students as the sample. Data were collected through observation sheets and questionnaires and analyzed using the paired sample t-test. The results showed an increase in the average activeness score from 75.41 (good category) in the pretest to 87.63 (excellent category) in the posttest. Furthermore, the proportion of highly active students increased from 74.2% to 93.5%. Statistical analysis yielded a p-value of 0.000 (p < 0.05), indicating a significant effect of the CPS model on improving student activeness. These findings suggest that the CPS model is a promising instructional strategy to enhance student engagement in Civic Education learning.Keywords: Creative Problem Solving, student activeness, Civic Education, innovative learning